Analisis Penjadwalan Proyek Dengan Penambahan Manpower dan Over Time Menggunakan Metode Time Cost Trade Off - Sri Puji Lestari; Widya Emilia Primaningtyas; Rina Sandora (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
A construction company in Karangpilang received a Pressure Vessel project. This project is delayed from the predetermined date so that a fine of 0.2% is imposed every day. So it is necessary to analyze project scheduling in order to get the maximum time and cost in this project. The methods used in this research are Time Cost Trade Off (TCTO), Precedence Diagram Method (PDM) and crashing. Acceleration is carried out on critical trajectories namely Marking/Catting, Rolling, Fit-Up, Welding, NDT, Primary Blasting and Top Coat. This study uses alternatives to increase over time and additional manpower. In this study, the maximum time and cost results were obtained with an alternative of 25% additional manpower. The resulting accelerated duration is 51 days faster than the actual duration, with costs incurred of Rp. 199,616,473, -, resulting in a decrease of 70% from the actual duration cost of Rp. 286,961,745, -. S curve analysis shows that the accelerated duration can be completed faster than the actual duration because the project can be completed on December 27, 2021. Where the accelerated duration is closer to the planned duration, namely November 26, 2021.